(Electronics and Photonics Division Award) Physics of Wide Band Gap Semiconductor Devices. (5th January 2017) - Shur, Michael
Abstract : Optical and electronic wide band gap devices have found important commercial applications. The device physics of all these devices is determined by the wurtzite (hexagonal) symmetry (leading to strong spontaneous and piezoelectric polarizations) and by a large polar optical phonon energy, which is the consequence of the strong bonding and small atomic masses of carbon and nitrogen. In AlGaN/GaN and AlGaInN/InGaN devices, the differences in the polarization at the heterointerfaces induce two-dimensional (2D) electron or hole gases at the interfaces (called "polarization doping") with densities over 4.4×10 13 cm 2 . Ballistic, overshoot, and electron runaway effects play a dominant role in short channel wide band gap devices now competing for applications in the terahertz (far infrared) range. In deep AlGaN ultraviolet (UV) Light Emitting Diodes (LEDs), fluctuations of the band gap determine the internal quantum efficiency, and the polarization induced percolating 2D hole gas is used for improved p-type contacts.